On the nature of the seismic ringing of the Moon. Analytical modeling. (July 2016) - Burmin, V.Yu.; Miroshnikov, V.V.; Fatyanov, A.G.
Abstract: The paper presents an analytical method for modeling of seismic wave fields at long distances. The method has no restrictions on the calculation accuracy, model of a medium and distance observations. It allows calculating the wave fields for large space-time scales characteristic of lunar experimental data. The most characteristic feature of the lunar seismograms is considerable duration of the seismic signal (seismic "ringing"). The seismic "ringing" on the Moon has been simulated based on the created program of calculation of wave fields.. Results of the simulation lead to the following conclusions. In a first approximation, a significant duration of the seismic "ringing" on the Moon can be explained by the resonance properties of a thin layer (regolith), without attracting the scattering effects due to the high degree of heterogeneity of the environment.